Screening for retinopathy of prematurity: evaluation and modification of guidelines - Larsson, E (Copyright 2002 British Journal of Ophthalmology, 2002)
Aims: To evaluate current screening guidelines for ROP (retinopathy of prematurity) and to determine whether they can be modified. Methods: In accordance with the authors’ present criterion, infants born in Stockholm County, Sweden, from 1 August 1998 to 31 July 2000, with a gestational age of ≤32 weeks, were screened for ROP. The effectiveness of screening was studied. Results: The incidence of ROP was 25.5% in this study. A dropout group comprising almost 20% of the population studied (≤32 weeks), was never referred, were lost to follow up, or died before screening was completed. No infant with a gestational age of >31 weeks at birth developed severe ROP (stages 3–5) and no infant with a gestational age of >29 weeks was treated for ROP. Conclusion: 80% of infants in this population with a gestational age at birth of ≤32 weeks, the current screening criterion, were effectively screened for ROP. The authors recommend that the screening criterion be lowered to ≤31 weeks since no infant with severe ROP would have been missed.